2023
DOI: 10.5114/pedm.2023.133122
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric obesity – time to act as early as possible

Joanna Szczyrska

Abstract: There has been a global increase in the average body mass index (BMI) in children and an alarming trend of increasing weight among the youngest children in recent decades. Childhood excess weight and obesity result in premature adult mortality and morbidity. Obesity is not only a risk factor for other diseases but is also a complex, multifactorial disease in its own right, linked to a genetic predisposition influenced by an increasingly permissive environment from intrauterine life throughout childhood and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…As health care clinicians, we make clinical decisions with the health of the child as our primary concern. Early discussion with families that obesity requires long-term care can create a supportive partnership with improved health for children [ 30 , 32 , 115 ]. Growing literature supports the need to address even our youngest patients with obesity with early, intensive, and effective comprehensive care [ [115] , [116] , [117] ].…”
Section: Anti-obesity Medication Use In the Child With Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…As health care clinicians, we make clinical decisions with the health of the child as our primary concern. Early discussion with families that obesity requires long-term care can create a supportive partnership with improved health for children [ 30 , 32 , 115 ]. Growing literature supports the need to address even our youngest patients with obesity with early, intensive, and effective comprehensive care [ [115] , [116] , [117] ].…”
Section: Anti-obesity Medication Use In the Child With Obesitymentioning
confidence: 99%
“…Early discussion with families that obesity requires long-term care can create a supportive partnership with improved health for children [ 30 , 32 , 115 ]. Growing literature supports the need to address even our youngest patients with obesity with early, intensive, and effective comprehensive care [ [115] , [116] , [117] ]. Severe obesity in the child is unlikely to remit [ 68 , 86 ].…”
Section: Anti-obesity Medication Use In the Child With Obesitymentioning
confidence: 99%
“…The findings of the 2019/2020 English National Child Measurement Program indicate that 9.9% of children aged 4-5 were classified as obese (5). Upon conducting a subsequent assessment of the same cohort at age 10-11, it was observed that the prevalence of obesity had escalated to 21% (5). Similarly, a recent systematic review conducted in China revealed a persistent and heterogeneous prevalence of overweight and obesity among children and adolescents in the country (6).…”
Section: Introductionmentioning
confidence: 99%
“…The escalating prevalence of childhood obesity is indicative of an ongoing trend (3,4). The findings of the 2019/2020 English National Child Measurement Program indicate that 9.9% of children aged 4-5 were classified as obese (5). Upon conducting a subsequent assessment of the same cohort at age 10-11, it was observed that the prevalence of obesity had escalated to 21% (5).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood overweight and obesity significantly predispose to metabolic disease at the adult age, indicating that preventive actions to curb obesity at a young age or preventing it altogether will have positive consequences on health later in life [ 1 ].…”
Section: Introductionmentioning
confidence: 99%